1995
DOI: 10.1161/01.hyp.26.6.1074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan on Blood Pressure, Metabolic Alterations, and Vascular Reactivity in the Fructose-Induced Hypertensive Rat

Abstract: Fructose feeding induces a moderate increase in blood pressure levels in normal rats that is associated with insulin resistance, hyperinsulinemia, and hypertriglyceridemia. The sympathetic nervous system seems to participate in the alterations of this model. To further explore the mechanisms underlying fructose-induced hypertension, the effects of the AT1 receptor antagonist losartan on blood pressure, insulin resistance, renal function, and vascular reactivity in mesenteric vascular beds were studied. Sprague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 22 publications
6
58
0
3
Order By: Relevance
“…Additionally, it has been reported that sucrose feeding increases norepinephrine excretion, turnover, and plasma concentration and enhances sympathetic nerve responses in rats (26,27). Thus sympathetic overactivity may be involved in the pathogenesis of this model, and may be responsible at least in part for the impairment of blood flow to skeletal muscle, which in turn would favor the development of insulin resistance (28). The finding that Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, it has been reported that sucrose feeding increases norepinephrine excretion, turnover, and plasma concentration and enhances sympathetic nerve responses in rats (26,27). Thus sympathetic overactivity may be involved in the pathogenesis of this model, and may be responsible at least in part for the impairment of blood flow to skeletal muscle, which in turn would favor the development of insulin resistance (28). The finding that Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Such locally generated angiotensin II could induce peripheral vasoconstriction, and could contribute to blood pressure elevation and insulin resistance. Consequently, it is possible that ARA exerts its beneficial effects by the suppression of the vascular actions of angiotensin II via AT1 receptor antagonism (28). This would reduce elevated blood pressure levels and restore a normal flow to the skeletal muscle, which would facilitate glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, há importante participação da Ang II. Estes resultados confirmam evidências anteriores da literatura nas quais, o bloqueio farmacológico do SRAA por inibidores da enzima conversora de angiotensina ou por antagonistas de receptores AT 1 foi capaz de normalizar a PA bem como a captação periférica de glicose 64,65 . Neste modelo, a hiperinsulinemia parece também desempenhar papel importante no desencadeamento da hiperatividade simpática uma vez que, em ratos, demonstrou-se, nestas condições, ativação simpática para diferentes tecidos, incluindo o renal 66 .…”
Section: -Obesidade E Ativação Simpáticaunclassified
“…Furthermore, renal cell growth and extracellular matrix (ECM) synthesis and degradation were modulated by Ang II, leading to glomerulosclerosis and interstitial fibrosis and consequently to advanced renal failure (8). It has also been shown that ACE inhibitor and the Ang II receptor blocker improve insulin sensitivity and reduce blood pressure in essential hypertension and fructose-induced hyperinsulinemic hypertensive rats (9)(10)(11). However, it is not clear whether a blunted response to Ang II is found in insulinsensitive animal models.…”
Section: Introductionmentioning
confidence: 99%